The Influence of Digital Literacy on Career Adaptability is Mediated by Students’ Mental Resilience - Sarmila, Mila; Mohammad Darul Fadli, Uus; Rosmawati, Ery (Research in Management of Technology and Business, 2026)
This study examines the effect of digital literacy on students’ career adaptability, with mental resilience as a mediating variable. The study addresses the issue of low career readiness among students in responding to the demands of a rapidly evolving digital work environment. A quantitative explanatory approach was applied using a sample of 115 Management students from Universitas Buana Perjuangan Karawang. Data were collected through a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that digital literacy has a positive and significant effect on both career adaptability and mental resilience. Mental resilience also has a significant effect on career adaptability. However, the mediation test shows that mental resilience does not significantly mediate the relationship between digital literacy and career adaptability. These findings suggest that digital literacy plays a direct and dominant role in enhancing students’ readiness to adapt to the digital labor market. The study highlights the importance of strengthening digital competencies and integrating resilience development into higher education curricula.